Kulttuurien tutkimuksen menetelmät - Fingerroos, Outi; Kajander, Konsta; Lappi, Tiina-Riitta (Tietolipas, 2022)
This collection deals with cultural studies in the humanities and the methods it uses. Its authors include scholars of ethnology, anthropology, folkloristics, digital culture research, and study of religions. Its chapters address topics of discussion and debate in humanistic culture research and indicate what tools are currently being used to study cultural phenomena. Various phases of the research process are covered, including epistemology, research ethics, techniques of data collection and analysis, the writing process of research plans, and the process of writing up the analysis. The book's authors contribute to our knowledge of changes in research paradigms and agendas, scientific philosophies, ethnographic fieldwork, different modes of writing, materiality, reflexivity, observation, researchers' use of the five senses, digital research, audiovisual techniques of observation, and selected textual methodologies. The book is intended as a textbook and methods guide for students in the fields of cultural research, for postdoctoral researchers, and for more senior researchers.